Formulasi Model Pengembangan Pendidikan Islam: Kajian Integrasi Madrasah, Sekolah dan Perguruan Tinggi dengan Pesantren - Ni'mah, Zetty Azizatun (Didaktika Religia, 2016)
Pesantren is an educational institution after the recitation of the Qur'an in the entire territory of Indonesia. Pesantren distinctive shape and varied makes its presence continues to grow, but a significant development came after an intercourse with the school system or also known as the madrasa system. The growth of Islamic madrasah education is a response to the school system that has been the policy of the Dutch government within the framework of ethical politics. Growth and development of madrasas in the early 20th century is part of the Islamic reform movement in Indonesia, which has a fairly intensive contacts with the reform movement in the Middle East. One form of the dynamics and development of the earliest schools is the mixing between the boarding school system with madrasa system. Both institutions, initially stood alone. Model of teaching at a boarding school in the classical delivered in the mosque or surau with sorogan method, while teaching models delivered modern madrassa in the class room with a varied methods. Marriages between boarding school with this madrasah, has brought a lot ofÂ progress in the world of boarding schools. Model Integration madrasah/boarding school is divided into four, namely: Full Integration, Integration Selective, Instrumental Integration, and Integration Minimal. The meeting point of the integration of schools with madrassas, Islamic schools and Islamic Universities with Pesantren or vice versa is equally Aiming internalization of Islamic values, independence, sincerity and simplicity and personality formation holistic: an individual can find the identity, purpose and meaning in life through relation to society, spiritual values that can address the challenges and needs of the times.